2000
DOI: 10.1023/a:1001907806062
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The personality characteristics of male clients of female sex workers and their motivations for seeking the services of sex workers were examined. It was hypothesized that clients of sex workers would differ from nonclients in that they would adopt less feminine sex roles, exhibit lower social-sexual effectiveness, and show higher levels of sensation-seeking behavior. Sixty-six clients of sex workers and 60 nonclients volunteered to complete a short questionnaire to assess demographic characteristics, sex role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…This suggests that moderation analyses could identify specific groups (e.g., high sensation seekers) that might benefit from interventions. Given that male clients of FSWs may be more likely to seek sexual sensation than non-clients (Xantidis & McCabe, 2000), targeted sociocognitive interventions are recommended that take into account characteristics such as gender and the propensity to seek novel sexual experiences that may influence self-efficacy for condom use (Donohew et al, 2000). …”
Section: Discussionmentioning
confidence: 99%
“…This suggests that moderation analyses could identify specific groups (e.g., high sensation seekers) that might benefit from interventions. Given that male clients of FSWs may be more likely to seek sexual sensation than non-clients (Xantidis & McCabe, 2000), targeted sociocognitive interventions are recommended that take into account characteristics such as gender and the propensity to seek novel sexual experiences that may influence self-efficacy for condom use (Donohew et al, 2000). …”
Section: Discussionmentioning
confidence: 99%
“…These factors group the main reasons for paying for sexual services that have been mentioned in studies on this subject (Jordan 1997;McKeganey and Barnad 1996;xantidis et al 2000;Kinnell 2006;Månsson 2006;Della Giusta et al 2009;Marttila 2003). However, this study has gone further, given that based on these motivational factors an important contribution is offered: the classification or typology of buyers in function of their reasons for paying for sexual services.…”
Section: Discussionmentioning
confidence: 99%
“…This type of buyer could be a collaborator in the detection and reporting of victims of trafficking for sexual exploitation, given that their ultimate aim makes them more likely to be sensitive to the life circumstances of the women who provide sexual services. Finally, we highlight the group called Riskers: those buyers who enjoy risk and dominating in sexual relationships, who are attracted by the forbidden and for whom paying for sexual services is an element of masculine identity, or who are seeking new sensations and clandestine relationships (McKeganey and Barnad 1996;xantidis et al 2000). It is possible that among these buyers are those who want sexual practices without protection because they perceive risk differently (Leonard 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding further highlights the importance of addressing sexual expectancy on alcohol use especially among FSWs who are at higher risk for excessive drinking and alcohol-induced unprotected sex (Kumar, 2003; Panchanadeswaran et al, 2008; Zachariah et al, 2003). Because alcohol may also be used to enhance sexual experiences by FSWs’ male clients, who usually have more power over FSWs in deciding condom use (Blanc, 2001; Pulerwitz, Amaro, De Jong, Gortmaker, & Rudd, 2002; Xantidis & McCabe, 2000), it is highly suggested that interventions which attempt to modify expectancy of alcohol as a sex facilitator to target both FSWs and their clients in order to be effective. Venue based interventions is a potential way to address alcohol use behaviors for both FSWs and male clients (Samet et al, 2010b).…”
Section: Discussionmentioning
confidence: 99%